2016
DOI: 10.1209/0295-5075/116/53001
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional localization of an atom with sub-half-wavelength spatial resolution via coherently controlled spontaneous emission

Abstract: We propose a scheme for two-dimensional sub-half-wavelength atom localization using two lasers with equal frequencies, and obtain the analytical expression of conditional position probability (CPP) using a spontaneous-emission spectrum for a four-level atom which passes through two-dimensional orthogonal standing-wave fields. The quantum interference effect between two decay channels leads to extreme spectral narrowing and quenching of spontaneous emission in some regions of the standing-wave field, which resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Studies of two-dimensional (2D) atomics system can further demonstrate spatial structure of atomic positions [26][27][28][29][30][31][32][33]. It is possible to use population measurements, controlled spontaneous emission [34][35][36][37][38][39], probe absorption [40][41][42][43][44] and gain [45], Ramandriven coherence [46], and interacting double-dark resonances to localize the atom in 2D space [47]. Proite and partners [48] investigated a proof-of-principle experiment and observed that the atomic-level population is localized in space using the electromagnetically induced transparency.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of two-dimensional (2D) atomics system can further demonstrate spatial structure of atomic positions [26][27][28][29][30][31][32][33]. It is possible to use population measurements, controlled spontaneous emission [34][35][36][37][38][39], probe absorption [40][41][42][43][44] and gain [45], Ramandriven coherence [46], and interacting double-dark resonances to localize the atom in 2D space [47]. Proite and partners [48] investigated a proof-of-principle experiment and observed that the atomic-level population is localized in space using the electromagnetically induced transparency.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] In the current decade, the interest in high-dimensional atom localization has been increased due to its unique aspects and enormous applications. Many schemes have been proposed based on probe absorption, [30][31][32] spontaneous emission [33,34] and squeezed vacuum. [35] Ivanov et al [36] proposed a four-level tripod system and used the population of the excited states to localized an atom in two dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above approaches for localization, considerable effort has recently been expended on the precise positioning of emitters by means of position-dependent standing-wave (SW) laser fields. Due to the spatial-dependent interaction between the quantum emitter and SW fields, the positional information of the object can be obtained by measuring the probe absorption spectrum [15,16,17,20] or the spontaneously emitted photons [18,19,20]. Generally, in order to realize one-dimensional (1D) localization, we just need the SW fields aligned in one direction [21,22].…”
Section: Introductionmentioning
confidence: 99%